P78 Comparisons of the metabolic consequences among adolescents with different severity of obesity: A three-year longitudinal cohort study. (18th November 2019) - Hsiao, YC; Wang, JH; Wang, YY; Lin, JS; Chen, MC; Chang, YC
Abstract : Aim: Adolescent obesity is an important issue, especially severe obesity which will increase the risks of future morbidity and life quality. Our study aims to define the impact of severe childhood obesity in term of metabolic consequences. Methods: Nineteen obese adolescents were enrolled due to abnormal body mass index (BMI) categorized as obesity (95th percentile of BMI). They were further divided into two groups: obesity (n=14) versus severe obesity (n=5). Severe obesity was defined as the BMI greater than 120% of the 95th percentile BMI of their age and gender. Data collections by questionnaire included the demographics, family history of metabolic related diseases, sleep schedules, the habit of daily exercise and diet, and awareness of their health issue. Postural related vital signs change and the data of serum biochemical profile were also detected. Result: Sixty-three percent (12/19) of these obese children belonged the category of obesity at their 1st grade of the elementary school. Subjects of severe obesity had significantly higher body weight and BMI (both p=0.002*) at 1st grade, bigger waist circumference (p=0.046*) at 4th grade if compared with obese subjects. No significant finding was measured in hypertension, orthostatic changes, and SpO2 among these two groups. There was no significant difference in family history of metabolic related diseases (hypertension, diabetes, heart disease, and weight problems). Comparisons of serum biochemical profile among these two groups showed significant differences including higher uric acid (p-value=0.039*), total bilirubin (p-value=0.030*), triglyceride (p-value=0.018*), and low density lipoprotein (p-value=0.018*). Statistical trends were noted in the followings: blood urea nitrogen (p-value=0.064), total cholesterol (p-value=0.07), and gamma-glutamyltransferase (p-value=0.075). The prevalence of metabolic syndrome was 10.5% (2/19) in this study, and without statistically significant if compared among these two groups (7.1% vs. 20%, p-value=0.468). Conclusion: Subjects with severe obesity tend to have bigger waist circumference at 4th grade. Although the prevalence of metabolic syndrome among these two groups didn't show statistical significance, the biochemical profile including elevated triglyceride, low-density lipoprotein, total bilirubin and uric acid which might be good markers for early detections of metabolic changes in severe obesity.